Development of early age autogenous and thermal strains of alkali-activated slag-fly ash pastes - Lacante, Maïté; Delsaute, Brice; Gambacorta, Julie; Königsberger, Markus; Staquet, Stéphanie (Frontiers in Built Environment, 2022)
Replacing ordinary Portland cement-based materials with alkali-activated industrial wastes is often limited because of significant volume changes occurring in these materials at early age. This experimental study aims to quantify the extent of the volume changes and explore the underlying mechanisms of pastes composed of slag and fly ash (ratio 50:50) which are activated by sodium hydroxide and sodium silicate. Eight compositions were tested, with silica modulus (Ms) varying between 1.04 and 1.58 and with solution-to-binder ratios (S/B) varying between 0.47 to 0.70. Specimen length changes in sealed conditions are monitored by applying repeated thermal variations in an adapted AutoShrink device and are accompanied by isothermal calorimetry, uniaxial compressive strength, and internal relative humidity (IRH) tests. This way, the temporal evolutions of autogenous strains, the coefficient of thermal expansion (CTE), the heat release, the apparent activation energy (Ea), the IRH and the strength are determined and compared to each other. Both the measured autogenous shrinkage and CTEs are rather large; they amount to 4000-5000 μm/m and roughly 40 μm/m/°C, respectively, at material ages of two weeks. An increase in S/B leads to a decrease in autogenous shrinkage and an increase in CTE. An increase in the Ms causes a decrease in both the autogenous shrinkage and the CTE. Most strikingly, autogenous shrinkage evolves linearly with the cumulative heat released by the binders. The IRH remains continuously above 94% during the first two weeks. The apparent activation energy amounts to roughly 74 kJ/mol and is virtually unaffected by S/B and Ms.